Educational Trajectories Among Young Indigenous Women in Amazonia: A Quest for Gender Equity and Interculturality. - Ames, Patricia; Morelli, Camilla; Aguirre, Almendra Aguilar; Desi, Roldan Tumi (Anthropology & Education Quarterly, 2025)
This article examines a growing demand for higher education among Indigenous Amazonian women, exploring their educational goals and the challenges they face. We examine how young women's desire to access new educational opportunities is entwined with an aspiration to become new kinds of persons, but also to support their own communities. We argue that women's demand for education is actively shaping new futures, opening new pathways toward educational inclusion and leadership on their own terms.